1999
DOI: 10.1098/rspb.1999.0687
|View full text |Cite
|
Sign up to set email alerts
|

Market forces predict grooming reciprocity in female baboons

Abstract: We argue that grooming is a commodity that female primates can trade, either for itself or in exchange for other services (sensu biological markets theory) and that the decision to do either will depend on the degree of competition within a social group. We test this using data from four chacma baboon troops, living in two populations that di¡er markedly in the degree of contest competition. As predicted by the predominance of grooming dyads in which females are closely ranked there was, in all four troops, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
298
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(316 citation statements)
references
References 20 publications
16
298
1
1
Order By: Relevance
“…During the night, Japanese macaques have been observed to huddle more frequently with kin and familiar social partners [28], and as temperatures get colder, the size of their huddling clusters increases [14]. We did not collected data on the time individuals spent in contact with their conspecifics at night, so we could not directly test the link between survival and the amount of time an individual spent huddling at night [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the night, Japanese macaques have been observed to huddle more frequently with kin and familiar social partners [28], and as temperatures get colder, the size of their huddling clusters increases [14]. We did not collected data on the time individuals spent in contact with their conspecifics at night, so we could not directly test the link between survival and the amount of time an individual spent huddling at night [28].…”
Section: Discussionmentioning
confidence: 99%
“…We considered an individual's time spent feeding, the number and quality of their social relationships, sex and rank as the potential predictors of survival. We predicted that individuals that were more likely to survive the cold winter were: (i) those that spent more time feeding, as they would be in better physical condition, in terms of fat reserves, and more effective at fulfilling the energetic requirements of thermoregulation [1]; (ii) those with a higher number and, on average, higher quality of social relationships, as they would gain the social benefits of feeding tolerance [14,15] and behavioural thermoregulation (i.e. huddling: [1,16]); (iii) females, owing to their smaller body mass and reduced energetic demands compared with males [17] and (iv) high ranking individuals, who tend to get preferential access to food [18].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, this has been interpreted as a (relatively) short-term temporal contingency. For example, both Seyfarth & Cheney (1984) and Hemelrijk (1994) showed that previous grooming may increase the probability of agonistic support, and both Barrett et al (1999) and Manson et al (2004) showed that monkeys timematch grooming given and received during each grooming session.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the concept has since been used (sometimes referred to as 'dominance gradient') in several behavioural studies such as biological market models (e.g. Barrett et al 1999;Leinfelder et al 2001) and theoretical modelling studies by Hemelrijk (1999) and Hemelrijk & Gygax (2004), who used the coefficient of variation as a measure of rank differentiation. The concept is further pivotal in the realms of social power and dominance styles (Flack &de Waal 2004) andreconciliation (e.g.…”
mentioning
confidence: 99%